The Impact of PUBG Gaming on Cognitive, Psychological, and Academic Outcomes: A Multidimensional Empirical Study in Benghazi, Libya - Naeima Aeiad Hamad Alarifi (Journal of Scientific and Human Dimensions, 2026)
This study provides a comprehensive, multidimensional analysis of the psychological, cognitive, behavioral, and academic impacts of prolonged engagement with Player Unknown’s Battlegrounds (PUBG) within the socio-cultural context of Benghazi, Libya. Using a cross-sectional quantitative design (n = 200), the research integrates advanced statistical techniques, including Pearson correlation, independent samples t-tests, and multiple regression modeling, to examine the relationships between gameplay intensity, anxiety levels, executive function disruption, and academic performance. The findings reveal a statistically significant positive correlation between daily gameplay duration and anxiety levels (r = 0.48, p < 0.01), alongside a strong negative association with academic performance (r = -0.52, p < 0.01). Regression results further confirm gameplay intensity as a robust predictor of both increased anxiety (β = 0.44) and decreased academic outcomes (β = -0.49), explaining approximately 41% of the variance (R² = 0.41). Moreover, children exhibited significantly higher levels of executive dysfunction, sleep disruption, and chronic procrastination compared to adults, indicating heightened neurodevelopmental vulnerability. The study introduces the concept of the “Digital Vacuum,” referring to the structural absence of physical recreational alternatives, which amplifies dependency on virtual environments. The findings are interpreted through established theoretical frameworks, including Time Displacement Theory, Self-Determination Theory, and Neurocognitive Load Theory. The study concludes with strategic recommendations at both policy and educational levels, emphasizing the integration of digital hygiene programs and the development of alternative socio-recreational infrastructures.